Impact of the Suissano Health Programme on antimicrobial usage on 291 pig farms in Switzerland. Issue 1 (29th June 2020) - Echtermann, Thomas; Müntener, Cedric; Sidler, Xaver; Kümmerlen, Dolf
Abstract : Background: In 2015, in Switzerland the Suissano Health Programme was implemented in pig production to improve transparency for antimicrobial usage (AMU) and to reduce the usage of fluoroquinolones (FQ), macrolides and cephalosporins, representing highest priority critically important antimicrobials. Methods: In the presented cohort study, the impact of the Suissano programme on the AMU of 291 pig farms between 2016 and 2017 was investigated. AMU was calculated in total numbers of defined course doses (nDCDch) for all farms in the programme. For each single farm the nDCDch/animal/year was determined for four different age categories (suckling piglets, weaned piglets, fattening pigs, sows) as well as each antimicrobial substance separately. Trends between 2016 and 2017 were investigated for all farms as well as the 25 per cent with the highest usage of antimicrobials (high users) separately. Results: Total AMU measured in nDCDch declined by 23 per cent between 2016 and 2017, but statistically significant differences could not be observed when comparing the data sets of the individual farms. A significantly reduced usage of FQ could be demonstrated in suckling piglets (P=0.003), weaned piglets (P=0.006) and sows (P=0.008) in 2017 compared with 2016. For high users, a significant reduction of total AMU could be shown in suckling piglets (P=0.02), weaned piglets (P=0.0004) and fattening pigs (P=0.01). Conclusion: This study demonstrated a significant reduction in the usage of FQs in suckling piglets, weaned piglets and sows as well as total AMU in suckling piglets, weaned piglets and fattening pigs on high‐usage farms.